RESISTANCE BAND TRAINING ON THROW-IN DISTANCE IN TERMS OF ARM MUSCLE STRENGTH OF 11-15 YEAR OLD SSB GAMA FC STUDENTS - wijaya, febri; Sumantri, Riyan Jaya; Azizah, Alfiah Rizqi; Syarif, Ahmad; Irawan, Yogi Ferdy; Widodo, Puput; Parmadi, Mokhamad; Burhaein, Erick; Santoso, Rahmawan; Khusnul, Anisa Isna; Irkham, Khafid (MEDIKORA, 2024)
AbstractThis study aims to determine the effect of resistance band training on throw-in distance in terms of arm muscle strength in soccer players aged 11-15 years. This type of research is a quantitative descriptive study using a quasi-experimental method with a two group pretest-posttest design, where one control group and one treatment group. The research subjects were 24 people. The sample was selected through purposive sampling. The test instrument to measure throwing distance is a meter and arm muscle strength using the push-up test. This study uses descriptive tests to describe the minimum, maximum, and average values, homogeneity tests using Kolmogorov-Smirnov, influence tests using One-Sample T-Test and correlation tests using Pearson. The results showed that (1) there was an effect of giving resistance band training on arm muscle strength with a sig value. 0.00. (2) there is an effect of resistance band training on throw-in distance (p=0.00); (3) there is a relationship between arm muscle strength and throw-in distance which can be seen from the sig value of 0.383> than r table. The conclusion obtained in this study is that arm muscle strength affects the throwing distance of SSB GAMA FC studentsAbstrakPenelitian ini bertujuan untuk mengetahui pengaruh latihan resistance band terhadap jarak throw in di tinjau dari kekuatan otot lengan pada pemain sepak bola usia 11-15 tahun. Jenis penelitian ini merupakan penelitian deskriptif kuantitatif dengan menggunakan metode quasi eksperimental dengan rancangan two grup pretest-posttest design, Dimana satu kelompok kontrol dan satu kelompok perlakuan. Subjek penelitian berjumblah 24 orang. Sampel dipilih melalui purposif sampling. Instrument tes untuk mengukur jarak lemparan adalah meteran dan kekuatan otot lengan menggunakan push-up test. Penelitian ini menggunakan uji deskiptif  untuk mengambarkan nilai minimal, maksimal, dan rata-rata, uji normalitas menggunakan Kolmogorov-Smirnov, uji pengaruh menggunakan One-Sample T-Test dan  uji korelasi menggunakan pearson. Hasil penelitian menunjukkan bahwa (1) terdapat peengaruh pemberian latihan resistance band terhadap kekuatan otot lengan dengan nilai sig. 0.00. (2) terdapat pengaruh latihan resistance band terhadap jarak throw in  (p=0.00); (3) terdapat hubungan antara kekuatan otot lengan dengan jarak throw in yang dapat di lihat dari nilai sig 0.383 > daripada r tabel. Kesimpulan yang diperoleh dalam penelitian inii adalah latihan resistance band berpengaruh pada peningkatan kekuatan otot lengan yang mempengaruhi jarak throw ini Siswa SSB GAMA FC.